Plasmodium knowlesi malaria in humans is widely distributed and potentially life threatening - Cox-Singh, J.; Davis, T.M.E.; Lee, K.; Shamsul, S.S.G.; Matusop, A.; Ratnam, S.; Rahman, H.A.; Conway, D.J.; Singh, B. (Oxford University Press, 2008)
Human infection with P. knowlesi, commonly misidentified as the more benign P. malariae, are widely distributed across Malaysian Borneo and extend to Peninsular Malaysia. Because P. knowlesi replicates every 24 h, rapid diagnosis and prompt effective treatment are essential. In the absence of a specific routine diagnostic test for P. knowlesi malaria, we recommend that patients who reside in or have traveled to Southeast Asia and who have received a "P. malariae" hyperparasitemia diagnosis by microscopy receive intensive management as appropriate for severe falciparum malaria.